Digital Platform Elaboration Skills for Islamic Religious Education Teachers - Husaini, Faiq; Hanif, Ahmad Dzaki Nur; Rahman, Ridwan Nur; Kahfi, Gaesa; Salsabila, Unik Hanifah (Journal of Islamic Education and Ethics, 2025)
This article tries to integrate digital platforms and presents how the most effective flow to be used in PAI learning, especially in the context of educational technology materials. This literature study focused on the analysis of various journals, articles, and related websites. This research aims to explore the potential of Google Classroom in improving the quality of Islamic Religious Education (PAI) learning. Drawing on the related literature, this study analyzed how PAI teachers can leverage Google Classroom to create more effective, engaging, and interactive learning. An analysis of various journals and related articles was also conducted. It can be seen that Google Classroom has great potential in improving the quality of PAI learning. Allows teachers to create a more flexible and engaging learning environment for students. Additionally, integration with other platforms such as Google Docs, YouTube, Google Slides, and other platforms allows teachers to present a more varied range of learning materials. However, the study also identified several shortcomings in the use of Google Classroom, such as network limitations, originality of student answers, and teachers' understanding of technology. Therefore, we tried to improve the quality of teachers' understanding of Google Classroom because it can be an effective tool in improving the quality of PAI learning.